Via verde e via d'oro Le politiche open access dell'Università di Firenze - Guerrini, Mauro; Mari, Giovanni (Studi e saggi, 2015)
Via verde e via d'oro. Le politiche open access dell'Università di Firenze addresses the multifaceted issue of free and open access to knowledge. Open access is a movement born in the last century with the aim of improving the dissemination of scientific knowledge. Over the last ten years, the movement has experienced a growth of interest due to the positions taken by the most important research institutes of the world, and to the legislative interventions of political and academic bodies. This publication analyses the reality of open access from the different points of view of the people who bring it to life: authors, publishers, academic world, legislators, users of knowledge, etc. The University of Florence, which is among the major players in the promotion of open access in Italy, has long been following the march in favour of open access, through the use of the green road with FLORE, its institutional repository, and of the gold road with Firenze University Press (FUP), whose publications have been available through open access since the early 2000s.